Faithful Transgressions In The American West Six Twentieth-Century Mormon Women's Autobiographical Acts - Bush, Laura (University Press of Colorado, 2004)
The central issue Bush finds in these works is how their authors have dealt with the authority of Mormon Church leaders. As she puts it in her preface, "I use the phrase 'faithful transgression' to describe moments in the texts when each writer, explicitly or implicitly, commits herself in writing to trust her own ideas and authority over official religious authority while also conceiving of and depicting herself to be a 'faithful' member of the Church." Bush recognizes her book as her own act of faithful transgression. Writing it involved wrestling, she states, "with my own deeply ingrained religious beliefs and my equally compelling education in feminist theories that mean to liberate and empower women." Faithful Transgressions examines a remarkable group of authors and their highly readable and entertaining books. In producing the first significant book-length study of Mormon women's autobiographical writing, Bush rides a wave of memoir publishing and academic interest in autobiography and other life narratives. As she elucidates these works in relation to the religious tradition that played a major role in shaping them, she not only positions them in relation to feminist theory and current work on women's life writings but ties them to the long literary tradition of spiritual autobiography.